2005
DOI: 10.1038/sj.eye.6702046
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pterygium on a tropical island in the Riau Archipelago

Abstract: Objectives To describe the epidemiology of pterygium among residents of an island in Indonesia and to examine the roles of age and gender as determinants of bilaterality and severity of the disease. Methods Voluntary eye screening on Pulau Jaloh, Riau Archipelago, Indonesia. Gender difference was tested using the v 2 test. The difference in age between subjects with and without disease was tested using unpaired Student's t-test. Odds ratio (relative risk) for gender was calculated using logistic regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
4
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 16 publications
(53 reference statements)
6
49
4
5
Order By: Relevance
“…These results are similar to those by other studies, and most of them confirm that there is a correlation between pterygium and age. [4][5][6][11][12][13][15][16][17] In this study, we found that a VA worse than 20/40 in the better eye is five times more likely among people with pterygium, and although this factor has been assessed in a limited number of studies, they support our findings. This can be due to a change in the convexity of the cornea and development of astigmatism.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results are similar to those by other studies, and most of them confirm that there is a correlation between pterygium and age. [4][5][6][11][12][13][15][16][17] In this study, we found that a VA worse than 20/40 in the better eye is five times more likely among people with pterygium, and although this factor has been assessed in a limited number of studies, they support our findings. This can be due to a change in the convexity of the cornea and development of astigmatism.…”
Section: Discussionsupporting
confidence: 81%
“…Some reports indicate that pterygium prevalence rates are lower than 2.0% where Compared to almost all other studies, the prevalence of pinguecula is relatively low in Tehran, and the only report indicating similar results concerns a study in Australia with a prevalence of 1.2% in Melbourne. 4 In contrast to the studies in Tehran and Melbourne, higher prevalence rates have been reported in other populations; 6,7,[11][12][13][14][15][16][17] even as high as 33.1 and 23% in China and Carolina, respectively (Table 4). 5,14 In this study, the prevalence of pterygium according to gender was higher in men only in the 20-to 39-year-old age group, and no significant correlation was seen between pterygium and gender in other age groups.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…15 In the Blue Mountain Eye Study, the prevalence was 7.3% for participants aged 49 years or older. 21 The prevalence of pterygium among 477 residents on a tropical island in Indonesia, however, was high, at 17.0%, 22 and the black population of the Barbados Eye Study was even higher, 23.4% of 2617 participants were aged 40-84 years. 23 The highest prevalence of pterygium, to our knowledge, was in subjects aged 50 years or above in a rural area of southern China, 33.01%.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive studies of freshwater swamp forest fish have been carried out in only a few regions such as Thailand, central Sumatra, Peninsular Malaysia and the Riau Archipelago (e.g. Tan & Tan, 1994;Vidthayanon, 2002;Tan & Kottelat, 2009), and all indications point to even greater fish diversity in unexplored locations.…”
Section: Aquatic Fauna In Freshwater Swamp Forestsmentioning
confidence: 99%